Longitudinal Neuropsychological Assessment in Two Elderly Adults With Attention-Deficit/Hyperactivity Disorder: Case Report - Klein, Margarete; Silva, Maria Aparecida; Belizario, Gabriel Okawa; Rocca, Cristiana Castanho de Almeida; Padua Serafim, Antonio De; Louzã, Mario R. (Frontiers in Psychology, 2019)
The neuropsychological deficits in ADHD may present clinical features similar to mild and/or major neurocognitive disorder and may act as a confounding factor as well as making it difficult to detect a cognitive decline. In this paper we present the results of longitudinal neuropsychological evaluations in two elderly women with ADHD. Three neuropsychological assessments were performed in two women with ADHD (60 and 77 years old) between 2010 to 2013 at intervals varying from 12 to 15 months. We use the structural magnetic resonance imaging to rule out significant abnormalities that could account for cognitive impairment. The results showed two different cognitive profiles with fluctuations in their performances along these two years was found, sometimes with improvement, sometimes with worsening of some functions such as attention, memory, inhibitory control and reaction time. To minimize confounding aspect of theses fluctuations in clinical practice, we considered a longer follow up with the application of a reliable change index (RCI) and a minimum of three spaced assessments as a baseline cognitive profile more consistent. Our findings not indicate a consistent cognitive decline and it contributes to a less pessimistic perspective about cognitive impairments could be a prodrome of ADHD-related dementia.